Intuitionistic Logic with Strong Negation - Gurevich, Yuri (Studia Logica, 1977)
Classical logic is symmetric with respect to True and False but intuitionistic logic is not. We introduce and study a conservative extension of first-order intuitionistic logic that is symmetric with respect to True and False.